Core-shell-shaped copper-manganese-based composite nano material, preparation method thereof and application of core-shell-shaped copper-manganese-based composite nano material in adsorption of elemental mercury in natural gas
By preparing core-shell copper-manganese-based composite nanomaterials, the problem of low adsorption efficiency of elemental mercury in natural gas in the prior art is solved, and efficient and stable mercury adsorption effect is achieved at room temperature, which is suitable for the demercury process of natural gas.
Patent Information
- Application Number
- CN202411566733.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-07
AI Technical Summary
The existing natural gas demercury adsorbents perform excellently in high temperature and flue gas environments, but are low in efficiency in normal temperature natural gas. The poor dispersion of copper species leads to insufficient active sites, affecting the adsorption efficiency of mercury.
Core-shell copper-manganese-based composite nanomaterials are prepared by hydrothermal reaction and calcination, and the combination of hollow manganese dioxide nanoparticles and divalent copper salts and amino-containing complexes are used to form adsorption with high specific surface area and rich active sites. Agent is suitable for adsorption of elemental mercury in natural gas at room temperature.
It has achieved efficient adsorption and long-term stability in normal temperature natural gas, the removal rate of elemental mercury reaches 99.8%, and maintains excellent performance in sulfur-rich aqueous natural gas.
Smart Images

Figure CN119258977A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of prevention and treatment of heavy metal pollutants in natural gas, and in particular to a core-shell copper-manganese-based composite nanomaterial, a preparation method thereof, and application thereof in adsorbing elemental mercury in natural gas. Background Art
[0002] At present, natural gas accounts for 25% of global fuel consumption. It is a high-quality, economical and efficient clean energy. Natural gas is a C1-C4 hydrocarbon gas mainly composed of methane, and contains a small amount of impurities such as hydrogen sulfide, carbon dioxide, water, and mercury. Mercury in natural gas mainly comes from the thermal maturity of source rocks and hydrothermal origin. With the exhaustion of shallow oil and gas fields, the enrichment of harmful impurities such as mercury in oil and gas in deeper reservoirs and high-temperature reservoirs has increased significantly. Among them, a small amount of hydrogen sulfide and mercury can cause environmental pollution, catalyst poisoning, and amalgam corrosion damage of heat exchangers. Mercury is a highly toxic heavy metal element, and its bioaccumulation and mobility threaten human health and environmental ecology. Mercury in natural gas usually exists in the form of elemental mercury, which becomes the main mercury species in natural gas due to its relatively low solubility and high volatility. In order to meet the ever-increasing environmental protection standards, the Natural Gas Standard (GB17820-2018) stipulates that the hydrogen sulfide and total sulfur content in liquefied natural gas feed gas and the extremely low concentration threshold of mercury are limited, and requires deep purification in the desulfurization and demercuration unit. Therefore, the development of stable, efficient and economical adsorbents for natural gas mercury removal is crucial for safe production and ultra-low emissions.
[0003] The main methods of demercuration of natural gas include adsorption, low-temperature separation and solution absorption. Weighing the demercuration accuracy, secondary pollution and application cost in different demercuration processes, adsorption is the most promising way to demercurate natural gas at home and abroad. Sulfur-loaded activated carbon, silver-loaded molecular sieve and metal oxide or sulfide-based adsorbents are the most widely used in natural gas demercuration devices. Sulfur-loaded activated carbon improves the surface adsorption of elemental mercury by the material. It is easy to produce capillary condensation with water and leaching of active component sulfur in a humid atmosphere, thereby limiting the contact between mercury and active component sulfur. At the same time, regeneration requires more than 600°C, otherwise it will become toxic solid waste and cause serious environmental problems. Silver-loaded molecular sieves react with silver and mercury to form silver-mercury alloys to achieve the purpose of demercuration. It has high demercuration efficiency, mature technology, strong renewability, and is suitable for higher removal accuracy and reaction space velocity, but it has poor water resistance and a relatively expensive unit price.
[0004] In addition, transition metal oxide adsorbents are rich in weakly basic lattice oxygen sites and basic hydroxyl functional groups, and are suitable for both dry gas and wet gas atmospheres containing water and acidic gases. They are regenerable and have the advantages of recycling and stable adsorption. Their excellent mercury removal performance is due to the valence change of transition metals. They can form redox cycles and strong metal ion affinity between high and low valence states, and have regeneration potential. In addition, in the presence of water vapor, hydrogen sulfide is easily decomposed on the surface of metal oxides, thereby enhancing the adsorption capacity of hydrogen sulfide. Once the adsorption reaches saturation, the metal oxides will be transformed into the corresponding metal sulfides, which can then be used to remove elemental mercury. Among transition metal oxides, manganese is the transition metal element with the second highest abundance in the earth's crust after iron. Its oxide has a strong reactivity. The crystal structure of α-MnO2, the most common manganese dioxide, is composed of 2×2 octahedral [MnO6] chains with common edges. The chains are connected by oxygen atoms at the vertices of the octahedral [MnO6] with common edges, forming a one-dimensional channel of about 0.46nm×0.46nm. The acid sites and easily releasable lattice oxygen in the channel structure make it promising for separation and catalytic applications. The most widely used in the existing technology is in the fields of selective adsorption catalytic oxidation and pollutant control. Copper oxide shows high efficiency in removing hydrogen sulfide. From a thermodynamic point of view, the sulfidation equilibrium constant of copper oxide reacting with hydrogen sulfide is the highest. Due to its inherent anisotropic growth characteristics, the in-situ converted copper sulfide is rich in unsaturated sulfur sites and exhibits the best mercury removal performance among all metal sulfides.
[0005] At present, there are related reports on mercury adsorbents. Patent CN201810829805.5 discloses a modified activated coke for demercuration of sulfur-containing flue gas and its preparation method. The invention discloses that metal oxides are loaded on the surface of activated coke, and the metal oxides are selected from copper oxide, manganese dioxide, cobalt tetraoxide, cerium dioxide, iron trioxide, and vanadium pentoxide. The activated coke used has a high specific surface area, which is conducive to the transmission and diffusion of gaseous pollutants, and overcomes the shortcomings of high price and low mechanical strength of activated carbon. Among them, copper oxide and manganese dioxide have excellent performance in the adsorption of mercury, but sulfur dioxide and nitrogen oxides present in flue gas may also affect the oxidation state of surface active species, thereby affecting the control efficiency of mercury. Patent CN201710873847.4 discloses a renewable and recyclable mercury adsorbent and its preparation and regeneration method. The invention discloses the preparation of mercury adsorbent using copper salt, chelating agent, and soluble manganese salt, and the successful preparation of spinel crystal copper manganate mercury adsorbent by coordination of complexes such as citric acid or oxalic acid. However, the adsorbents prepared by the above two preparation methods are only for the adsorption and removal of mercury in the flue gas atmosphere. There is a problem of insufficient number of active sites due to poor dispersion of copper species on the surface or inside of the carrier, so the adsorption and removal of mercury performance is poor. Summary of the invention
[0006] The object of the present invention is to provide a core-shell copper-manganese-based composite nanomaterial, a preparation method thereof, and an application in the adsorption of elemental mercury in natural gas. The core-shell copper-manganese-based composite nanomaterial has a high specific surface area, highly dispersed alkaline sites, and a good structure that is easy to diffuse and transfer. In a reducing natural gas atmosphere containing hydrogen sulfide and water, the core-shell copper-manganese-based composite nanomaterial has relatively excellent activity and long-term stability in the adsorption of elemental mercury.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a core-shell copper-manganese-based composite nanomaterial, comprising the following steps:
[0009] The hollow manganese dioxide nanoparticles, the divalent copper salt, the amino-containing complex and water are mixed to carry out a hydrothermal reaction to obtain a hydrothermal product;
[0010] calcining the hydrothermal product to obtain a core-shell copper-manganese-based composite nanomaterial;
[0011] The amino-containing complex comprises at least one of urea, ammonium oxalate and ethylenediaminetetraacetic acid.
[0012] Preferably, the preparation method of the hollow manganese dioxide nanoparticles comprises:
[0013] The tetraethyl orthosilicate, ethanol and alkaline aqueous solution are mixed and subjected to a hydrolysis reaction to obtain silicon dioxide nanoparticles;
[0014] The dispersion of the silicon dioxide nanoparticles is mixed with a potassium permanganate solution, reduced, and then etched under alkaline conditions to obtain hollow manganese dioxide nanoparticles.
[0015] Preferably, the divalent copper salt includes at least one of copper sulfate, copper nitrate, copper acetate and copper chloride.
[0016] Preferably, the molar ratio of the divalent copper salt to the hollow manganese dioxide nanoparticles is 1:10-20.
[0017] Preferably, the molar ratio of the divalent copper salt to the amino-containing complex is 1:150-200.
[0018] Preferably, the temperature of the hydrothermal reaction is 120-180° C., and the time is 12-24 hours.
[0019] Preferably, the calcination conditions include: a calcination temperature of 300-400° C., a holding time of 2 hours, an air atmosphere, and a heating rate of 2-5° / min to the calcination temperature.
[0020] The present invention provides a core-shell copper-manganese-based composite nanomaterial prepared by the preparation method described in the above technical solution.
[0021] The present invention provides the use of the core-shell copper-manganese-based composite nanomaterial described in the above technical solution in adsorbing elemental mercury in natural gas.
[0022] Preferably, the natural gas is sulfur-rich and water-containing natural gas, and the concentration of hydrogen sulfide in the natural gas is 100 to 300 ppm.
[0023] The invention provides a method for preparing a core-shell copper-manganese-based composite nanomaterial. Hollow manganese dioxide nanoparticles are mixed with divalent copper salt and amino-containing complexes, and hydrothermal treatment is performed to obtain the core-shell copper-manganese-based composite nanomaterial. The invention uses hollow manganese dioxide nanoparticles as shells, uses divalent copper salts and amino-containing complexes to carry out surface complexation and dispersion on the shell material, and then calcines to obtain the core-shell copper-manganese-based composite nanomaterial. Among them, oxygen atoms and nitrogen atoms in the amino-containing complex can provide lone pairs of electrons to form coordination bonds with the coordinated metal ions, and the amino groups in the amino-containing complex can form stable amino-containing complexes with various ions to improve its metal dispersibility. Therefore, the copper content in the prepared composite material is low, and the surface dispersibility is good. In a low-temperature natural gas atmosphere, the metal oxide is used as a mercury adsorbent to convert elemental mercury into stable mercuric sulfide, which has broad application prospects in the field of natural gas demercurization.
[0024] The copper-manganese-based composite nanomaterial prepared by the present invention has a core-shell structure, and the core-shell structure has a high specific surface area, a relatively fast diffusion rate, mechanical stability, and is suitable for large-scale industrial application requirements. The core-shell copper-manganese-based composite nanomaterial loaded with elemental copper prepared by the present invention has a high specific surface area, highly dispersed alkaline sites, and a good structure that is easy to diffuse and transfer. In a reducing natural gas atmosphere containing hydrogen sulfide and water, it has relatively excellent activity and long-term stability for the adsorption of elemental mercury.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] (1) Conventional metal oxide-based mercury adsorbents are usually used in flue gas environments with relatively high temperatures (60-150°C), but are not suitable for the temperature range required for natural gas demercuration (30-60°C). The core-shell copper-manganese-based composite nanomaterial mercury adsorbent of the present invention is designed for the atmosphere and temperature of the approximate working conditions of natural gas demercuration adsorption, and is suitable for the natural gas demercuration process at room temperature.
[0027] (2) The material has excellent copper dispersibility, easy diffusion and mass transfer structure, and abundant active sites, so it has numerous mercury adsorption active sites and active centers, which can effectively meet the adsorption of hydrogen sulfide and the removal of elemental mercury in the sulfur-rich and water-containing natural gas atmosphere.
[0028] (3) This material can adsorb mercury in natural gas rich in hydrogen sulfide and convert it into mercury sulfide, thereby achieving permanent removal of elemental mercury. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a SEM image of the silicon dioxide nanoparticles prepared in Example 1;
[0030] Figure 2 XRD pattern of silicon dioxide nanoparticles prepared in Example 1;
[0031] Figure 3 The XRD pattern of the hollow manganese dioxide nanoparticles prepared in Example 1;
[0032] Figure 4 The SEM images of the hollow manganese dioxide nanoparticles prepared in Example 1 at different magnifications, where a is 50,000 times and b is 16,000 times;
[0033] Figure 5 The SEM images of the hollow manganese dioxide nanoparticles prepared in Example 2 at different magnifications, where a is 50,000 times and b is 16,000 times;
[0034] Figure 6 The nitrogen adsorption-desorption isotherm diagram of the core-shell copper-manganese based composite material prepared in Example 1;
[0035] Figure 7 The figure is a temperature-programmed desorption diagram of oxygen of the core-shell copper-manganese-based composite material prepared in Example 1;
[0036] Figure 8 This is a SEM image of the core-shell copper-manganese based composite material prepared in Example 1;
[0037] Fig. 9 The XRD pattern of the core-shell copper-manganese based composite material prepared in Example 1;
[0038] Fig.10 This is a SEM image of the core-shell copper-manganese based composite material prepared in Example 2;
[0039] Fig.11 This is an X-ray energy spectrum scan of the core-shell copper-manganese based composite material prepared in Example 2. DETAILED DESCRIPTION
[0040] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0041] The present invention provides a method for preparing a core-shell copper-manganese-based composite nanomaterial, comprising the following steps:
[0042] The hollow manganese dioxide nanoparticles, the divalent copper salt, the amino-containing complex and water are mixed to carry out a hydrothermal reaction to obtain a hydrothermal product;
[0043] calcining the hydrothermal product to obtain a core-shell copper-manganese-based composite nanomaterial;
[0044] The amino-containing complex comprises at least one of urea, ammonium oxalate and ethylenediaminetetraacetic acid.
[0045] The invention mixes hollow manganese dioxide nanoparticles, divalent copper salt, amino-containing complex and water, and performs hydrothermal reaction to obtain a hydrothermal product.
[0046] In the present invention, the method for preparing the hollow manganese dioxide nanoparticles preferably comprises:
[0047] The tetraethyl orthosilicate, ethanol and alkaline aqueous solution are mixed and subjected to a hydrolysis reaction to obtain silicon dioxide nanoparticles;
[0048] The dispersion of the silicon dioxide nanoparticles is mixed with a potassium permanganate solution, reduced, and then etched under alkaline conditions to obtain hollow manganese dioxide nanoparticles.
[0049] In the present invention, the alkaline aqueous solution preferably includes at least one of ammonia water, sodium hydroxide aqueous solution, sodium carbonate aqueous solution and sodium bicarbonate aqueous solution; more preferably ammonia water; when the alkaline aqueous solution is two or more of the above, the present invention has no special limitation on the ratio of different types of alkaline aqueous solutions, which can be adjusted according to actual needs; the mass concentration of the alkaline aqueous solution is preferably 30%; the volume ratio of the tetraethyl orthosilicate, the alkaline aqueous solution and ethanol is preferably 1:0.8-0.85:11.5-12, more preferably 1:0.8:11.5.
[0050] In the present invention, ethanol and alkaline aqueous solution are preferably added first, and ethyl orthosilicate is added dropwise under heating in a water bath at 25° C., and stirred for hydrolysis.
[0051] In the present invention, the temperature of the hydrolysis reaction is preferably 20-30°C, more preferably 25°C; the time is preferably 12-48h, more preferably 24h. After the hydrolysis reaction is completed, the present invention preferably centrifuges the obtained product and washes it with water three times to obtain silica nanoparticles.
[0052] In the present invention, the concentration of the potassium permanganate solution (the solvent is water) is preferably 2-3 g / L, more preferably 2.2-3 g / L; the mass ratio of the silicon dioxide nanoparticles to the potassium permanganate in the potassium permanganate solution is preferably 0.03-0.15:1, more preferably 0.05-0.13:1.
[0053] The present invention preferably disperses the silicon dioxide nanoparticles in water by ultrasonic method to obtain a dispersion of the silicon dioxide nanoparticles, and then drops a potassium permanganate solution into the dispersion of the silicon dioxide nanoparticles under ultrasonic conditions.
[0054] In the present invention, the reduction temperature is preferably room temperature, and the reduction time is preferably 11 to 13 hours, more preferably 12 hours.
[0055] After the reduction, the present invention preferably centrifuges the product, washes it with water three times, and then etches the product.
[0056] In the present invention, the etching agent used in the etching treatment is preferably at least one of sodium carbonate, sodium hydroxide and potassium hydroxide, and more preferably sodium hydroxide; when the etching agent is two or more of the above, the present invention has no special limitation on the ratio of different types of etching agents, and any ratio is acceptable; the etching agent is preferably used in the form of an etching aqueous solution, and the concentration of the etching aqueous solution is preferably 1.5 to 2.5 mol / L, and more preferably 2 mol / L.
[0057] The present invention has no special limitation on the dosage of the etching reagent, which can be adjusted according to actual needs to ensure complete etching.
[0058] In the present invention, the etching temperature is preferably 55-65° C., more preferably 60° C.; the etching time is preferably 11-13 h, more preferably 12 h.
[0059] After the etching treatment, the present invention preferably centrifuges the obtained product and washes it with water three times to obtain hollow manganese dioxide nanoparticles.
[0060] The invention forms silicon dioxide by hydrolysis, then the silanol groups on the surface of silicon dioxide react with potassium permanganate to obtain a manganese dioxide-coated silicon ball product, and then the silicon is removed by etching to form birnessite crystal-type manganese dioxide.
[0061] In the present invention, the divalent copper salt preferably includes at least one of copper sulfate, copper nitrate, copper acetate and copper chloride; when the divalent copper salt is two or more of the above, the present invention has no special limitation on the ratio of different types of divalent copper salts, and any ratio is acceptable.
[0062] In the present invention, the molar ratio of the divalent copper salt to the hollow manganese dioxide nanoparticles is preferably 1:10-20, more preferably 1:20.
[0063] In the present invention, the amino-containing complex includes at least one of urea, ammonium oxalate and ethylenediaminetetraacetic acid, and more preferably urea; when the amino-containing complex is two or more of the above, the present invention has no special limitation on the ratio of different types of amino-containing complexes, and any ratio is acceptable.
[0064] In the present invention, the molar ratio of the divalent copper salt to the amino-containing complex is preferably 1:150-200, more preferably 1:160-180, and further preferably 1:173.
[0065] The present invention has no particular limitation on the amount of water used, and the amount of water used can be adjusted according to actual needs to ensure that the reaction proceeds smoothly.
[0066] The present invention preferably disperses hollow manganese dioxide nanoparticles in water to obtain a dispersion; prepares a divalent copper salt and an amino-containing complex into an aqueous solution, and stirs and mixes the dispersion with the amino-containing complex aqueous solution for 30 minutes to perform a hydrothermal reaction.
[0067] In the present invention, the temperature of the hydrothermal reaction is preferably 120-180° C., more preferably 120-150° C.; the time is preferably 12-24 h, more preferably 12 h.
[0068] During the hydrothermal reaction, copper salt and amino-containing complex (producing free amino groups) form copper complex in the hydrothermal reaction system. The amino-containing complex will decompose to produce ammonia and carbon dioxide during the hydrothermal process. Ammonia can form copper complex with copper ions, affecting the migration and precipitation behavior of copper ions. The ammonia produced by the decomposition of the amino-containing complex can be used as a reducing agent to promote the reduction process of copper ions. At the same time, the hydroxyl and amine groups on the surface of the amino-containing complex will bond with the surface of manganese dioxide. The gas produced by the decomposition of the amino-containing complex may form pores in the manganese dioxide. The dispersibility of the copper-ammine complex ion can be used as a structure-directing agent, and its dispersibility will affect the pore structure and morphology of the material.
[0069] After the hydrothermal reaction is completed, the present invention preferably centrifuges the obtained product, washes it with water three times, and calcines the obtained hydrothermal product.
[0070] In the present invention, the calcination conditions preferably include: a calcination temperature of 300-400°C, a holding time of 2h, an air atmosphere, and a heating rate of 2-5° / min to the calcination temperature; the calcination temperature is more preferably 350°C.
[0071] During the calcination process, the amino compound decomposes and releases carbon dioxide, and the copper ammonia complex is converted into copper oxide. After calcination, copper oxide is dispersed on the surface or inside of the hollow manganese dioxide, and the structure of the hollow manganese dioxide does not change.
[0072] The present invention takes into account the interaction between hydrogen sulfide and the adsorbent. Hydrogen sulfide in natural gas has acidic characteristics and reducibility. The chemical adsorption of hydrogen sulfide on the surface of the adsorbent is stronger than the physical adsorption. There is competitive adsorption between hydrogen sulfide and mercury. Excessive hydrogen sulfide will react with the active groups on the surface, reducing the sites available for mercury adsorption. At the same time, the presence of a sulfur-containing atmosphere makes it easy for hydrogen sulfide and the carrier to undergo a sulfidation reaction on the surface, generating acidic sites, causing the adsorption form of mercury to change from a free mercury binding reaction to mercuric sulfide. Moreover, the multivalent state conversion of manganese elements and the introduction of copper can activate oxygen species on the surface, increase the activity of oxygen species and the number of acidic sites. The multivalent state conversion of manganese is conducive to the migration and transformation of surface active oxygen species, and maintains the dynamic conversion balance between adsorbed oxygen and lattice oxygen. The sulfidation equilibrium constant of copper reacting with hydrogen sulfide is the highest, and the adsorption amount per unit mole is also much higher than that of other elements such as zinc, manganese, and calcium. Copper can also form a copper-mercury amalgam alloy with mercury, thereby producing an excellent capture effect on mercury.
[0073] The present invention provides a core-shell copper-manganese-based composite nanomaterial prepared by the preparation method described in the above technical solution. The present invention constructs a core-core structure in steps, can control the preparation of cores of different sizes, uses a seven-valent manganese source as an oxidant to grow and modify the surface of the shell, obtains hollow manganese dioxide as a shell material after etching, and then loads copper to form a core-shell structure copper-manganese-based composite nanomaterial.
[0074] The present invention adopts silicon dioxide spheres as templates, and can prepare a large number of manganese dioxide composite particles with controllable morphology in a single experiment with good repeatability.
[0075] The present invention provides the use of the core-shell copper-manganese-based composite nanomaterial described in the above technical solution in adsorbing elemental mercury in natural gas.
[0076] In the present invention, the natural gas is preferably sulfur-rich water-containing natural gas, and the concentration of hydrogen sulfide in the natural gas is 100 to 300 ppm, more preferably 200 ppm.
[0077] The present invention has no particular limitation on the specific components and sources of the natural gas, and any natural gas obtained in a manner well known in the art may be used.
[0078] In the present invention, the core-shell copper-manganese-based composite nanomaterial is preferably formed and granulated into 40-60 meshes and then used for adsorption of elemental mercury in a fixed bed under a natural gas atmosphere.
[0079] The application method of the present invention is not particularly limited and can be applied according to methods well known in the art.
[0080] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0081] Example 1
[0082] (1) According to the volume ratio of tetraethyl orthosilicate, 30% ammonia water and ethanol being 1:0.8:11.5, 26.4 mL of 30% ammonia water and 380 mL of ethanol were first added to a container, and 33 mL of tetraethyl orthosilicate was added dropwise at 25° C. and stirred for 24 h. After the reaction was completed, the product was centrifuged and washed with water three times to obtain silica nanoparticles;
[0083] (2) Dispersing 50 mg of the prepared silica nanoparticles in 50 mL of water, ultrasonically treating for 30 min to obtain a silica dispersion, weighing 1 g of potassium permanganate to prepare 450 mL of potassium permanganate aqueous solution, dripping the prepared potassium permanganate aqueous solution into the obtained silica dispersion drop by drop under ultrasonic conditions, stirring for 12 h, centrifuging the obtained manganese dioxide-coated silicon sphere product, washing with water three times, and dispersing in water to obtain a manganese dioxide-coated silicon sphere dispersion, weighing sodium hydroxide and dissolving it in water to obtain a sodium hydroxide aqueous solution with a concentration of 2 mol / L, dripping the sodium hydroxide aqueous solution evenly into the manganese dioxide-coated silicon sphere dispersion, and etching for 12 h in a water bath at 60° C., centrifuging the obtained product, and washing with water three times to obtain hollow manganese dioxide nanoparticles;
[0084] (3) According to the molar ratio of copper salt to hollow manganese dioxide nanoparticles being 1:20 and the molar ratio of copper salt to amino-containing complex being 1:173, 46 mg (0.19 mmol) of copper nitrate trihydrate and 2 g (33 mmol) of urea were weighed to prepare 50 mL of a mixed aqueous solution, 330 mg (3.8 mmol) of hollow manganese dioxide nanoparticles were dispersed in 20 mL of water, the resulting dispersion was added to the mixed aqueous solution, stirred for 30 min, and then transferred to a high-pressure reactor for hydrothermal treatment at 120 °C for 12 h. After the reaction was completed, the product was centrifuged and washed with water 3 times. The product was heated to 350 °C at a heating rate of 5 °C / min in an air atmosphere and kept warm for 2 h to obtain a core-shell copper-manganese-based composite nanomaterial.
[0085] Example 2
[0086] Large-scale synthetic experiments:
[0087] (1) According to step (1) in Example 1, 1 g of silicon dioxide nanoparticles was prepared;
[0088] (2) Dispersing 1 g of the prepared silica nanoparticles in 200 mL of water, ultrasonically treating for 30 min to obtain a silica dispersion, dissolving 7.5 g of potassium permanganate in 2.5 L of water to obtain a potassium permanganate aqueous solution, dripping the obtained potassium permanganate aqueous solution dropwise into the obtained silica dispersion under ultrasonic conditions, stirring for 12 h, centrifuging the obtained manganese dioxide-coated silicon sphere product, washing with water three times, dispersing the product in water to obtain a manganese dioxide-coated silicon sphere dispersion, weighing sodium hydroxide and dissolving it in water to obtain a sodium hydroxide aqueous solution with a concentration of 2 mol / L, dripping the sodium hydroxide aqueous solution evenly into the manganese dioxide-coated silicon sphere dispersion, and etching for 12 h in a 60° C. water bath to obtain 2 g of hollow manganese dioxide nanoparticles;
[0089] (3) According to the molar ratio of divalent copper salt to hollow manganese dioxide nanoparticles being 1:20 and the molar ratio of copper salt to amino-containing complex being 1:173, 46 mg of copper nitrate trihydrate solid and 2 g of urea were weighed to prepare 50 mL of mixed aqueous solution, 330 mg of hollow manganese dioxide nanoparticles were dispersed in 20 mL of water, the obtained dispersion was added to the mixed aqueous solution, stirred for 30 min, and then transferred to a high-pressure reactor for hydrothermal treatment at 120 °C for 12 h. After the reaction was completed, the product was centrifuged and washed with water 3 times. The product was heated to 350 °C at a heating rate of 5 °C / min in an air atmosphere and kept warm for 2 h to obtain a core-shell copper-manganese-based composite nanomaterial.
[0090] Characterization
[0091] Figure 1 This is a SEM image of the silicon dioxide nanoparticles prepared in Example 1. The nanoparticles are approximately spherical, and the average size thereof is 80 nm after calculation of the particle size statistical distribution.
[0092] Figure 2 The XRD pattern of the silicon dioxide nanoparticles prepared in Example 1 shows a broad and short peak, which belongs to the amorphous bulging peak of silicon dioxide, confirming that the product after hydrolysis is silicon dioxide.
[0093] Figure 3 This is the XRD diagram of the hollow manganese dioxide nanoparticles prepared in Example 1. It can be seen that the product is manganese dioxide with good crystallinity.
[0094] Figure 4 These are SEM images of the hollow manganese dioxide nanoparticles prepared in Example 1 at different magnifications, where a is 50,000 times and b is 16,000 times. It can be seen that the product is block-shaped nanoparticles.
[0095] Figure 5The SEM images of the hollow manganese dioxide nanoparticles prepared in Example 2 at different magnifications, a is 50,000 times, b is 16,000 times, and the results show that the morphology and size of the hollow manganese dioxide nanoparticles synthesized on a large scale do not change significantly, proving the feasibility of large-scale synthesis of the material. It shows that the nanomaterial has the advantages of controllable morphology and good repeatability.
[0096] Figure 6 This is a nitrogen adsorption-desorption isotherm diagram of the core-shell copper-manganese-based composite material prepared in Example 1, and the inset is the pore size distribution of the sample. Figure 6 It can be seen that the composite material has a type IV adsorption isotherm and a H3 type hysteresis loop. When the relative pressure is greater than 0.8, it is proved that its structure contains a slit-shaped mesoporous structure with a relatively concentrated pore volume distribution and an average pore diameter of 14.73 nm.
[0097] Figure 7 The temperature-programmed desorption of oxygen of the core-shell copper-manganese-based composite material prepared in Example 1 is shown in FIG. Figure 7 It can be seen that the desorption peak at low temperature (<200 °C) is the desorption peak of physically adsorbed oxygen species, while the desorption peak at 200-350 °C is usually due to the desorption of chemically adsorbed oxygen and surface activated oxygen, which is attributed to the weakly chemically adsorbed oxygen (O α The peak above 350°C is attributed to lattice oxygen (O β ), and the main desorption peak between 300-500 °C indicates that these oxygen species are highly reactive, indicating that the material has a strong surface oxygen storage capacity and abundant lattice oxygen sites.
[0098] Figure 8 This is the SEM image of the core-shell copper-manganese based composite material prepared in Example 1. Figure 8 It can be seen that the samples after hydrothermal and calcination are better than hollow manganese dioxide particles ( Figure 4 ), the product appears in fragments.
[0099] Fig. 9 This is the XRD diagram of the core-shell copper-manganese-based composite material prepared in Example 1. Compared with the hollow manganese dioxide, its crystallinity is slightly reduced, and a low diffraction peak belonging to copper oxide is observed.
[0100] Fig.10 This is the SEM image of the core-shell copper-manganese based composite material prepared in Example 2, which is consistent with the morphology of Example 1 and is in the form of porous fragments.
[0101] Fig.11 This is an X-ray energy spectrum scan of the core-shell copper-manganese based composite material prepared in Example 2, and the inset shows the mass percentage of the elements in the scanned area; Fig.11From the EDS spectrum, we can see that the sample contains the elements Mn, O, Cu, Si, and C, which proves the successful synthesis of the material.
[0102] The present invention uses a hard template silicon ball to cover the surface and then etch it to form a core-shell structure. Figure 2 , Figure 3 and Fig. 9 The decrease in the intensity of the bulge peak attributed to the original amorphous silicon in XRD, and Fig.11 The mass content of various elements in EDS can prove the etching process of the core structure. There is still a small amount of silicon that cannot be completely etched away, so a core-shell structure appears in the microstructure.
[0103] Test Case
[0104] 0.25 mL of the core-shell copper-manganese-based composite nanomaterial prepared in Example 1 and granulated to 40-60 mesh was weighed and placed in a laboratory simulated fixed bed reactor, the temperature of the water bath was adjusted, gaseous elemental mercury was generated through a mercury permeation tube, and the elemental mercury concentration at the inlet and outlet of the reactor was monitored in real time by a VM-3000 mercury meter.
[0105] The gas composition is:
[0106] During the full atmosphere evaluation, the gas composition, flow rate and evaluation time are as follows: 60% methane as carrier gas, 15% carbon dioxide, 5% water vapor, 200ppm hydrogen sulfide, and the rest is nitrogen balance gas. The total gas rate is 1L / min and the evaluation time is 2h.
[0107] When evaluating the methane nitrogen atmosphere: methane is used as 60% carrier gas and the remaining 40% is nitrogen balance gas.
[0108] The above two atmospheres were pre-introduced with the atmosphere gas to be tested for background baseline calibration. After a period of time, when the concentration in the pipeline stabilized at 0, the valve of the methane carrier gas line passing through the mercury permeation tube was opened. After a period of stabilization, the mercury concentration was finally recorded, and then the filling adsorption was performed. The initial mercury concentration of the above two atmospheres was 100±1μg / m 3 , the adsorption temperature is 35℃.
[0109] The results show that the initial mercury concentration in methane-nitrogen atmosphere is 100.1 μg / m 3 After treatment, the mercury concentration at the outlet was 4.2 μg / m 3 ;
[0110] Full atmosphere: initial mercury concentration 101.0 μg / m 3 After treatment, the mercury concentration at the outlet is 0.2 μg / m 3 ;
[0111] Calculation formula: Removal rate η = (c 入口 -c出口 ) / c 入口 *100%
[0112] Thus, the adsorbent described in Example 1 had a removal efficiency of 95.8% under methane and nitrogen conditions, and a removal efficiency of 99.8% for elemental mercury in the presence of all gases.
[0113] The adsorption product of the mercury adsorbent prepared in Example 1 under a methane-nitrogen atmosphere is mercuric oxide; while the adsorption product of the adsorbent under all gas conditions is mostly mercuric sulfide, with a small amount of mercuric oxide. In a methane-nitrogen atmosphere, due to the lack of sulfides, metal oxides or metal sites on the surface of the adsorbent may directly react with mercury to form mercuric oxide. This reaction may involve oxygen vacancies or metal sites with higher oxidation states on the surface of the adsorbent, which can capture and oxidize gaseous elemental mercury. In the full atmosphere, the presence of sulfide H2S significantly affects the demercuration mechanism of the adsorbent. Sulfides can react with mercury to form mercuric sulfide. The strong sulfur affinity of the surface metal leads to the formation of mercuric sulfide, which reduces the concentration of mercury in the gas phase, thereby improving the demercuration efficiency.
[0114] It can be seen from Example 1 that the core-shell copper-manganese-based composite nanomaterial prepared by the present invention has excellent performance in removing mercury from natural gas.
[0115] According to the test method of Example 1, the composite nanomaterial prepared in Example 2 was used for mercury removal test in the above two atmospheres, and the mercury concentrations before and after the two atmospheres were:
[0116] Methane nitrogen atmosphere: initial mercury concentration 99.7 μg / m 3 After treatment, the mercury concentration at the outlet is 4.5 μg / m 3 Full atmosphere: initial mercury concentration 100.5 μg / m 3 After treatment, the mercury concentration at the outlet is 0.1 μg / m 3 .
[0117] The results show that the mercury removal activity of the composite nanomaterial prepared in Example 2 is 95.5% under the conditions of methane and nitrogen, and the removal rate of elemental mercury is 99.9% in the presence of all gases.
[0118] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a core-shell copper-manganese-based composite nanomaterial, characterized in that: The following steps are involved: The hollow manganese dioxide nanoparticles, the divalent copper salt, the amino-containing complex and water are mixed to carry out a hydrothermal reaction to obtain a hydrothermal product; calcining the hydrothermal product to obtain a core-shell copper-manganese-based composite nanomaterial; The amino-containing complex comprises at least one of urea, ammonium oxalate and ethylenediaminetetraacetic acid.
2. The preparation method according to claim 1, characterized in that: The preparation method of the hollow manganese dioxide nanoparticles comprises: The tetraethyl orthosilicate, ethanol and alkaline aqueous solution are mixed and subjected to a hydrolysis reaction to obtain silicon dioxide nanoparticles; The dispersion of the silicon dioxide nanoparticles is mixed with a potassium permanganate solution, reduced, and then etched under alkaline conditions to obtain hollow manganese dioxide nanoparticles.
3. The preparation method according to claim 1, characterized in that: The divalent copper salt includes at least one of copper sulfate, copper nitrate, copper acetate and copper chloride.
4. The preparation method according to claim 1 or 3, characterized in that: The molar ratio of the divalent copper salt to the hollow manganese dioxide nanoparticles is 1:10-20.
5. The preparation method according to claim 1 or 3, characterized in that: The molar ratio of the divalent copper salt to the amino-containing complex is 1:150-200.
6. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 120-180° C. and the time is 12-24 hours.
7. The preparation method according to claim 1, characterized in that: The calcination conditions include: a calcination temperature of 300-400° C., a heat preservation time of 2 hours, an air atmosphere, and a heating rate of 2-5° / min to the calcination temperature.
8. The core-shell copper-manganese-based composite nanomaterial prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the core-shell copper-manganese-based composite nanomaterial according to claim 8 in adsorbing elemental mercury in natural gas.
10. The use according to claim 9, characterized in that: The natural gas is sulfur-rich and water-containing natural gas, and the concentration of hydrogen sulfide in the natural gas is 100-300 ppm.
Citation Information
Patent Citations
Renewable cyclic utilization mercury adsorbent as well as preparation method and regeneration method thereof
CN107601570A
Modified active coke applied to mercury removal of sulfur-containing flue gas as well as preparation method thereof
CN108993504A